2005
DOI: 10.1111/j.1468-2311.2005.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Evidence for the Effectiveness of the Reasoning and Rehabilitation Programme

Abstract: Reasoning and Rehabilitation is a cognitive-behavioual training programme for offenders, accredited by the Home Office for use with offenders in prison and on custodial sentences in England and Wales. Evidence the programme achieves significant reductions in offending is questionable. A matched control study is reported which used both offending and psychometric outcome measures. Findings for reconviction are mixed. Offenders whose attitudes changed pro-socially were more likely to be reconvicted than were off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 17 publications
1
23
0
1
Order By: Relevance
“…These additional results should be considered preliminary unpublished data that were not peer-reviewed (Berman, personal communication, August 16, 2012). Wilkinson (2005) The treatment had little effect on reconviction. Paradoxically, when contrasting reoffending and not reoffending program completers, the group of reoffenders showed significantly more PCA change in the desired direction than those who did not recidivate.…”
Section: Intervention Studies Assessing General Pro-criminal Attitudementioning
confidence: 98%
See 1 more Smart Citation
“…These additional results should be considered preliminary unpublished data that were not peer-reviewed (Berman, personal communication, August 16, 2012). Wilkinson (2005) The treatment had little effect on reconviction. Paradoxically, when contrasting reoffending and not reoffending program completers, the group of reoffenders showed significantly more PCA change in the desired direction than those who did not recidivate.…”
Section: Intervention Studies Assessing General Pro-criminal Attitudementioning
confidence: 98%
“…McGuire, & Hatcher (2001) T C = 220 2 Offense-Focused problemsolving training Pre-and post-Test correlations All significant for Crime PICS II Questionnaire (Frude, et al, 1994) Pre (Walters, 1990(Walters, , 1998 Pre-Post treatment change -significant pre-post-increase on Outcome Expectancies for Crime Negative (OEC-NEG) Scale -no significant decrease for anticipated positive outcomes (Outcome Expectancies for Crime Positive Scale; OEC-POS) OEC-POS with 12 anticipated positive outcomes and four anticipated negative outcomes (OEC-NEG) (Walters 2000(Walters , 2003 -no changes on either scale for waiting list-control group Study 2 -clinically and statistically significant reductions on the PICTS Current scale for program participants independent from factors unique to the institution -significant alterations on both PICTS scales (decreases), but stronger deceleration on the Current scale scores -superiority of shorter programs 14. Wilkinson (2005) T IT =105 T C = 43 T NC = 62 C = 98 3 Reasoning and Rehabilitatio n (Ross ,& Fabiano, 1985) Reconviction (2yrs after intervention) -no difference in reconviction between offenders (R&R and controls) -program completers were less likely to be reconvicted than controls Attitude change pre-post-treatment -reconvicted Offenders: Revise likelihood of reoffending down -not reconvicted Offenders: revised self-assessment upwards, almost no change in Crimepics score(Criminality: Crime Pics Scale; Frude, Honess & Magurie, 1994), reported to be less selfcontrolled (Self-control; Rosenbaum, 1980), small downward shift in self-reported problems -> offenders whose attitude changes pro-social were more likely to be reconvicted than offenders whose attitude didn't changed positive 15. Witte, Di Placido, Gu, & Wong (2006) T C = 72 2 Clearwater Sex Offender Treatment Program…”
mentioning
confidence: 99%
“…However, while a recent meta-review suggests effect sizes between general criminal attitudes and recidivism are positive but modest (r ≈ 0.20; Banse et al, 2013), even this relationship has not always been found when Crimepics II is used (Wilkinson, 2005, Table 5). In essence, we can say that there was a positive change in crime attitude scores, and it is likely that this is due to experiencing the programme, but whether this affects rates of recidivism will require further work, and in particular using a design that not only compares attitudes across treatment and control conditions at the group level, but also allows the further assessment of correlations between individual attitude scores at the end of the programme and conviction rates at two years for each participant (this is required to extend the claim that not only does the treatment change attitude, but that this is the main causal pathway in any desistance effects observed, Banse et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the Wilkinson (2005) study a prosocial attitude scale was used and juvenile offenders whose attitudes changed prosocially were more likely to be re-convicted than offenders whose attitudes did not positively change. The reasons why research into the effectiveness of the R&R programme has demonstrated conflicting outcomes may be due to the fact that the programme was initially developed for adults and therefore it was not suitable for young offenders (Mitchell & Palmer, 2004).…”
mentioning
confidence: 99%